(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
The research aims to clarify the impact of cybersecurity risks on the efficiency and effectiveness of the external auditor in light of modern digital developments, by conducting an analytical study of the opinions of a sample of external auditors and specialized academics, regarding the impact of these risks and the necessary protection measures and their impact on the efficiency and effectiveness of the external auditor. The study assumed that there is a positive relationship between cybersecurity risks and the efficiency and effectiveness of the external auditor in light of digital developments. The research hypothesis was tested through a field study conducted on a sample that included a selected group of external auditors and specialized academics, using the descriptive analytical approach, adopting a questionnaire form and according to the five-point Likert scale for a random sample, through distributing (45) questionnaire forms, where (39) of them were retrieved as valid forms for the study, i.e. a response rate of (86.666%), as the answers of the external auditors, numbering (24) forms, were (61.54%), while The answers of the specialized academics, numbering (15) questionnaires, were (38.46%), while the unsuitable questionnaire for analysis was (6) neglected questionnaires, i.e. (13.333%), and the percentage was (86.666%), which is considered an excellent and acceptable percentage for the purposes of scientific research. For the purposes of analysis, the statistical program (SPSS) was relied upon in analyzing the answers of the research sample and presenting and interpreting the results. Among the most important results reached by the research: The weighted arithmetic means for all paragraphs of the impact of cybersecurity risks on the efficiency and effectiveness of the external auditor in light of modern digital developments, where the general weighted arithmetic mean for all answers reached (3.213) and a standard deviation of (0.635) and the table value (t) was (2.089), This is a high percentage, indicating that cybersecurity risks are having an impact on the efficiency and effectiveness of external auditors in light of recent digital developments, according to the opinions of external auditors and specialized academics, which has had a positive impact on the results. The study recommended the creation of a dedicated cybersecurity risk management department or unit in each company, ensuring continuous updates to the department in light of recent technological and digital developments, and providing ongoing training for cybersecurity personnel, developing their skills, and educating them about the seriousness and consequences of cyber threats, risks, and incidents.